Improving Job Quality for Direct Care Workers. Issue 2 (May 2019) - Osterman, Paul
The prevalence of low wage work is a major challenge for American labor markets and health care is an industry in which many of these low wage workers are found. This paper provides data documenting these facts and then discusses strategies for upgrading job quality for long-term care workers who constitute the majority of low wage employees in health care occupations. In addition the paper briefly discusses approaches for upgrading the employment opportunities of low wage employees who are in the health industry but in jobs that are not health care specific.